Effect of nutrient modification on growth and flavonone production from callus culture of Citrus grandis - Azlinda, Abdul Ghani; Zarina, Zakaria, Dr.; Ku Syahidah, Ku Ismail; Nor Alina, Nazri (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Kampus Pauh Putra, Arau, Perlis, Malaysia.